One-Step Synthesis of CaO-ZnO Efficient Catalyst for Biodiesel Production - Javier Toledo Arana; Juan José Torres; Diego F. Acevedo; Cristian O. Illanes; Nelio A. Ochoa; Cecilia L. Pagliero (International Journal of Chemical Engineering)
Biodiesel is the best candidate for fuel oil replacement, and to obtain it, heterogeneous catalysts offer large advantages: they can be separated from the product and reused. This work reviews a novel one-step synthesis of CaO-ZnO catalytic particles suitable for biodiesel production. The catalyst is synthesized using an original simple method that involves mixing of ZnO with CaCO3 and subsequent calcination. The CaO-ZnO microparticles obtained present an average size of 2 μm. This material shows the characteristic crystallographic cubic structure of CaO and the hexagonal phase of ZnO. The temperature-programmed reduction experiment evidences an interaction between CaO and ZnO. Moreover, the infrared spectroscopy shows typical bands of these compounds. The catalyst shows high biodiesel yield, up to 73% in the first cycle and 64% in the second one. In this work, the synthesis of an efficient CaO-ZnO catalyst with a huge potential is revealed, which could be an economic alternative to produce biodiesel.